Penyuluhan dalam Membangun Kesadaran Moral dan Etika di Era Digital bagi Ikatan Remaja Masjid Al-Lathifah Cikarang Barat - Badruzzaman, Aceng; Nugroho, Djoko; Miharja, Muhammad Najamuddin Dwi; Ermanto, Ermanto (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The implementation of this community service aims to increase moral and ethical awareness in the digital era among teenagers from the Al-Lathifah Mosque Youth Association, West Cikarang, through a structured and interactive counseling program. In its implementation, community service involves four main steps: preparation, planning, implementation, and evaluation. In the preparation stage, surveys and discussions were carried out to determine teenagers' needs regarding digital ethics. Next, at the planning stage, outreach materials are prepared thoroughly and delivery methods are chosen carefully. The outreach includes lectures, group discussions, and interactive activities designed to strengthen understanding and application of digital ethics in everyday life. Evaluation was carried out using questionnaires and in-depth interviews to measure changes in participants' understanding and attitudes. The results of this research show that there is a significant increase in digital moral and ethical awareness among teenagers after attending the counseling. This program has also succeeded in creating an environment that supports the development of better character. Thus, this outreach program has made a positive contribution to increasing digital moral and ethical awareness and could be an example for similar programs in the future.